Second malignancies after autologous haematopoietic stem cell transplantation following modified BEAM conditioning regimen in patients with Hodgkin lymphoma – characteristics and risk factors analysis - Czyż, Anna; Łojko-Dankowska, Anna; Matuszak, Magdalena; Dytfeld, Dominik; Kaźmierczak, Maciej; Komarnicki, Mieczysław (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : The aim of the study was to determine the incidence of second malignancies among patients with Hodgkin lymphoma (HL) treated with autologous haematopoietic stem cell transplantation (ASCT) following a modified BEAM (BCNU, etoposide, cytarabine, melphalan, dexamethasone) regimen between 1992 and 2012 at our department. We also intended to define the risk factors for the occurrence of second neoplasm after ASCT. Material and methods: T he long-term outcomes after transplant were evaluated in 170 patients, median age 31 years (range 17–61), who received a median of two pre-transplant chemotherapy lines (range 1–5). Results : MOPP (mechlorethamine, vincristine, procarbazine, prednisone) or MOPP-type regimens were given to 12% of patients prior to ASCT. The median follow-up of the survivors was 73 (12–242) months. The 7-year overall survival and progression-free survival were 75% and 64%, respectively. Second malignancies occurred in 7 of the 170 patients, including 5 haematological malignancies, and 2 solid tumors. They developed at a median of 8 years (range 0.4–13.5) from ASCT. The 10-year and 15-year cumulative incidence of developing a second malignancy were 7% and 13%, respectively. In multivariate analysis, age  40 years at transplant (HR = 8.8; p = 0.008) and pre-transplant MOPP-type chemotherapy (HR = 5.6; p = 0.030) were the only factors significant for developing a second malignancy. Conclusions : Our results indicate that age of patient and the type of pre-transplant chemotherapy contribute to the risk of the development of a second neoplasm after ASCT in patients with HL. We believe that better characterization of second malignancies and associated risk factors may be useful for clinicians who care for these patients.